Nitric oxide donors rescue diabetic nephropathy through oxidative‐stress‐ and nitrosative‐stress‐mediated Wnt signaling pathways. Issue 1 (25th July 2014) - Hsu, Yung‐Chien; Lee, Pei‐Hsien; Lei, Chen‐Chou; Ho, Cheng; Shih, Ya‐Hsueh; Lin, Chun‐Liang
Abstract Aims/Introduction The role of the renal nitric oxide (NO) system in the pathophysiology of diabetic nephropathy constitutes a very challenging and fertile field for future investigation. The purpose of the present study was to investigate whether NO donors can attenuate diabetic renal fibrosis and apoptosis through modulating oxidative‐ and nitrosative‐stress, and Wnt signaling using in vivo diabetic models. Materials and Methods Diabetic rat was induced by a single intraperitoneal injection of streptozotocin. Rats in each group were intraperitoneally given 2, 2′‐(hydroxynitrosohydrazino)bis‐ethanamine (1 U/kg/day) and vehicle for 28 and 56 consecutive days. Expression of the oxidative‐ and nitrosative‐stress, and Wnt signaling components were examined in kidneys from diabetic animals by quantitative reverse transcription polymerase chain reaction, western blot analysis and immunohistochemical staining. Results NO donor treatment significantly reduced the ratio of kidney weight to bodyweight and proteinuria. This treatment also significantly restored the suppressive effect of diabetes on urinary NO2 + NO3 levels. Immunohistochemistry showed that NO donor treatment significantly reduced transforming growth factor (TGF)‐β1, fibronectin, cleaved caspase‐3 and triphosphate‐biotin nick end‐labeling expression in the glomeruli of diabetic rats. We found that diabetes promoted 8‐hydroxy‐2′‐deoxyguanosine, and peroxynitrite expression coincided with reduced endothelial NO synthase expression in glomeruli. Interestingly, NO donor treatment completely removed oxidative stress and nitrosative stress, and restored endothelial NO synthase expression in diabetic renal glomeruli. Immunohistomorphometry results showed that NO donor treatment significantly restored suppressed Wnt5a expression and β‐catenin immunoreactivities in glomeruli. Based on laser‐captured microdissection for quantitative reverse transcription polymerase chain reaction, diabetes significantly increased TGF‐β1, and fibronectin expression coincided with depressed Wnt5a expression. NO donor treatment reduced TGF‐β1, fibronectin activation, and the suppressing effect of diabetes on Wnt5a and β‐catenin expression in renal glomeruli. Conclusions NO donor treatment alleviates extracellular matrix accumulation and apoptosis in diabetic nephropathy in vivo by not only preventing the diabetes‐mediated oxidative and nitrostative stress, but also restoring downregulation of endothelial NO synthase expression and Wnt/β‐catenin signaling. These findings suggest that modulation of NO is a viable alternative strategy for rescuing diabetic renal injury.